Hypolimnetic oxygenation and aeration in two Midwestern USA reservoirs. (3rd July 2019) - Austin, David; Scharf, Roger; Chen, Che-Fei; Bode, Jim
Abstract: Austin D, Scharf R, Chen C-F, Bode J. Hypolimnetic oxygenation and aeration in two Midwestern USA reservoirs. Lake Reserve Manage. 35:266–276. This study compares performance of hypolimnetic aeration (HA) with hypolimnetic oxygenation (HO) from 1988 to 2018, over multiple project phases and a baseline period 1984 to 1986. Saint Paul Regional Water Services, Minnesota, pumps 170 MLD (45 MGD) from the Mississippi River through a chain of 4 lakes before treatment. Two, Pleasant Lake and Vadnais Lake, were equipped with partial-lift HA later replaced by linear diffuser HO. Ferric chloride was injected into inflows and into Vadnais at the HA or HO system. HA failed to relieve hypolimnetic hypoxia in Pleasant (median DO 1.7 mg/L) or Vadnais (median DO 2.7 mg/L). Median HO values were aerobic (Pleasant 4.2 mg/L, Vadnais 8.5 mg/L). Both HA and HO raised hypolimnetic oxidation reduction potential to high positive values from negative values associated with Mn and Fe solubilization. Compared to HA, HO reduced median hypolimnetic total Mn concentrations by 75% in Pleasant and in 93% in Vadnais, and hypolimnetic total Fe by 84% in Pleasant and 81% in Vadnais. HA significantly lowered median hypolimnetic TP from baseline, 0.552 mg/L to 0.146 mg/L in Pleasant, and 0.533 mg/L to 0.045 mg/L in Vadnais. HO median hypolimnetic TP was significantly lower at 0.053 mg/L in Pleasant, 0.030 mg/L in Vadnais. Superior performance of HO occurred at similar oxygen delivery rates: 1775 kg/d in Pleasant and 970 kg/d in Vadnais, versus HA of 1200 kg/d in each lake. Performance differences are likely due to lower induced currents at the sediment surface by HO compared to HA.